2020
DOI: 10.3389/fped.2020.00499
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes and Baseline Risk Factors of Acute Kidney Injury in Children After Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Background: Acute kidney injury (AKI) is a frequent and widely recognized complication of allogeneic hematopoietic stem cell transplantation (allo-HSCT). Despite relatively high prevalence, AKI after allo-HSCT and its risk factors in children remain obscure. The aim of this study was to describe the prevalence and course of AKI during the first 100 days after allo-HSCT in children and to investigate its associations with baseline characteristics. Methods: Retrospective single-center chart review of all patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
(64 reference statements)
2
10
0
Order By: Relevance
“…The above-mentioned anomalies, both altering serum creatinine values and subsequently aggravating hyperfiltration, justify such assessment, although imperfect, among the hematological protocols of kidney function evaluation [32][33][34]. The concomitant existence of two eGFR values, before and just after HSCT, in one model indirectly confirms previous observations of high eGFR values' influence on AKI recurrence in HSCT children [11]. It also suggests the significance of a preserved renal functional reserve (RFR), represented here by the most prominent increase in eGFR value 24 h after HSCT versus the pre-transplantation record, for the prediction of AKI incidence [35,36].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The above-mentioned anomalies, both altering serum creatinine values and subsequently aggravating hyperfiltration, justify such assessment, although imperfect, among the hematological protocols of kidney function evaluation [32][33][34]. The concomitant existence of two eGFR values, before and just after HSCT, in one model indirectly confirms previous observations of high eGFR values' influence on AKI recurrence in HSCT children [11]. It also suggests the significance of a preserved renal functional reserve (RFR), represented here by the most prominent increase in eGFR value 24 h after HSCT versus the pre-transplantation record, for the prediction of AKI incidence [35,36].…”
Section: Discussionsupporting
confidence: 52%
“…Other studies confirm the influence of unrelated donors, underlining the additional roles of viral infections, malignant disease as the indication, drug nephrotoxicity, complications like thrombotic microangiopathy, or an older child's age, in aggravating the risk of AKI development after HSCT [6][7][8][9][10]. Recent data also point to the impact of initially increased estimated glomerular filtration rate (eGFR) values on further AKI recurrence [11].…”
Section: Introductionmentioning
confidence: 89%
“…Representative studies that focus on the association of AKI with transplant outcomes are shown in Table 2. In pediatric HCT recipient, the incidence of AKI is similar to adults (44,48,49,(56)(57)(58), AKI worsens mortality after HCT (49,57), and the 1-year survival rate is less than 10% in patients with renal failure requiring renal replacement therapy (56). Fortunately, HCT-related AKI has decreased in recent years due to the increased use of less toxic conditioning regimens, decreased rates of SOS, modified infection prophylaxis, less amphotericin B use, and declining rates of severe aGVHD (59,60).…”
Section: Kidney Disease After Hctmentioning
confidence: 99%
“…1). Among included studies, four were prospective and 16 were retrospective [10,11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. A total of 4,378 patients who underwent HSCT were included in the 20 studies, including 2,219 and 2,159 patients with and without AKI, respectively.…”
Section: Discussionmentioning
confidence: 99%